ETYMOLOGICAL AND LINGUACULTURAL STUDY OF BRAND NAMES STRUCTURED WITH THE HELP OF ANTHROPONOMYS (Academicia Globe: Inderscience Research, 2023)
The article talks about how anthroponyms play an important role in the formation of brand names. Help anthroponyms emerge. The system of proper nouns has a sizable collection of anthroponyms that represent nouns. When interacting with customers, the word "brand name" is increasingly used to refer to all of the characteristics of the product at once. The brand name's sonority and memorability play a key role in competing products. The primary purpose of brand names is to draw customer’s attention and set the product apart from competing products of a similar nature; sonority and memorability play a significant role in this. The adoption of such names accomplishes the following artistic goals: produce sonority and melodic quality through mimicry of words, taking into consideration